A New Structure of Geotextile Called Soil Nets for Reinforcement - Bo-Bo Xiong; Bin Tian; Xiao-chun Lu; Bo-Fu Chen (Advances in Materials Science and Engineering)
This paper proposes a new reinforcement structure called soil nets firstly, which is capable of strengthening foundations, slopes, and other structures with better effect than that of soilbags. This proposed geotextile structure typically contains several layers of soil net, which are placed in a unique way. One layer of soil net can be described as a collection of spherical soilbags that are connected together in two directions, one in which they are connected by ropes and another in which they are connected by the PP woven bags that contain the soil. A mechanical property analysis of the soil nets shows that the yield stress of the soil within the soil nets is improved, the tensile capacity of the soil nets is greater than that of the soil with which it is filled, and the equivalent coefficient of interlayer friction between the connected soil nets is larger than that for soilbags. Applications of this new reinforcement structure in the reinforcement of a foundation and a slope are considered, and the corresponding reinforcement effects are calculated. The calculation results demonstrate that the soil nets concept yields efficient reinforcement structures with many advantages.